A Systematic Mapping Study on Research Contributions on UX Evaluation Technologies - Rivero, Luis Rivero; Conte, Tayana Conte (Teste, 2018)
User eXperience (UX) refers to quality attributes related to the feelings and emotions of the users. In order to evaluate UX, several technologies (tools, methods, techniques, others) have been proposed that range from using questionnaires to employing biometrics. However, it is essential to characterize UX evaluation technologies to obtain evidence on the contexts in which using a specific technology can provide better evaluation results. In this paper, we present the state of the art on how to evaluate the UX of software applications. We performed a systematic mapping study with an initial sample of 2101 papers from which 227 relevant papers describing UX evaluation technologies have been identified. The results suggest that there is a need for specific UX evaluation technologies that are easy and comfortable to use from the point of view of users, while supporting practitioners in the correction of the aspects that cause poor experiences.